2015
DOI: 10.5812/ircmj.29536
|View full text |Cite
|
Sign up to set email alerts
|

Anbarnesa: The Past Tradition, the Future Medicine

Abstract: Context:In the Iranian traditional medicine, anbarnesa smoke derived from burning female donkey’s dung has long been used for treatment of inflammatory ulcers and infections of the middle and external ear with no significant side effects. The aim of this study was to introduce anbarnesa and discuss its therapeutic effects.Evidence Acquisition:We conducted a systematic search in PubMed, Medline, Google, and Google Scholar databases to find studies on anbarnesa. The keywords searched were as follows: “anbarnesa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Candida albicans is one of the common causes of fungal vaginal infections [13]. Avicenna has recommended Anbarnasara smoke to treat vaginal infections [11]. In this study, our results showed the antifungal activity of ASS at low concentrations on C. albicans, corroborating Avicenna's recommendation on using Anbarnasara for vaginal infections.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Candida albicans is one of the common causes of fungal vaginal infections [13]. Avicenna has recommended Anbarnasara smoke to treat vaginal infections [11]. In this study, our results showed the antifungal activity of ASS at low concentrations on C. albicans, corroborating Avicenna's recommendation on using Anbarnasara for vaginal infections.…”
Section: Discussionsupporting
confidence: 85%
“…In rural areas of Iran, Anbarnasara smoke is commonly used to treat infections. The healing effects of this traditional medicinal smoke have been reported in infected burn wounds, localized skin abscesses, sinusitis, and vaginal infections [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Donkey's dung (Anbarnesa) has an important role as a drug in Iranian Traditional Medicine. [21] Iron supplements when appropriate can prevent chronic liver diseases. [22] Siddha medicine also favors using iron in chendooram (sulfide form preferably in nanozie).…”
Section: Animal and Mineral Based Drugs Used For Liver Diseasesmentioning
confidence: 99%